Theory and Practice of Model Transformations : 8th International Conference, ICMT 2015, Held as Part of STAF 2015, L'Aquila, Italy, July 20-21, 2015. Proceedings - Kolovos, Dimitris; Wimmer, Manuel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Model Transformation, ICMT 2015, held in L'Aquila, Italy, in July 2015, as Part of STAF 2015, the federation of a number of the leading conferences on software technologies. The 16 revised papers were carefully selected from 34 submissions. The papers are organized in topical sections on change management; reuse and industrial applications; new paradigms for model transformation; transformation validation and verification; and foundations of model transformation.
Change Management -- Reuse and industrial applications -- New paradigms for model Transformation -- Transformation validation and verification.- Foundations of model transformation.
Keywords: Software engineering; Logic design; Computer science; Information Systems; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Management of Computing and Information Systems